Bacillus Bio-Organic Fertilizer Altered Soil Microorganisms and Improved Yield and Quality of Radish (Raphanus sativus L.) - Yingbin Qi; Zhen Wu; Yachen Wang; Rong Zhou; Liwang Liu; Yan Wang; Jiying Zhao; Fangling Jiang (Plants)
Excessive use of fertilizers will not only cause the enrichment of soil N nutrients, soil secondary salinization, soil acidification, and an imbalance of the soil microbial community structure, but will also lead to the nitrate content of vegetables and the ground water exceeding the standard. The application of bio-organic fertilizer could reduce the amount of mineral fertilizer used. However, the effects of nitrogen reduced with different bio-organic fertilizers on soil chemical properties, microbial community structure, and the yield and quality of radish are not clear. In a field experiment, we designed six fertilization treatments: no fertilization (CK), conventional fertilization (T1), a total nitrogen reduction of 20% (T2), and a total nitrogen reduction of 20% with “No. 1”, “Seek” or “Jiajiapei” bio-organic fertilizers. The results showed that nitrogen reduction of 20% with Bacillus bio-organic fertilizer (N1) significantly increased the organic matter, pH, total nitrogen content, and the relative abundance of Bacillus and Streptomyce in the soil compared with T1. RDA analysis showed that the pH, organic matter content, invertase and fluorescein diacetate enzyme activity of the soil were significantly correlated with the soil microbial community structure. In addition, the yield and Vc content in radish were increased with the application of bio-organic fertilizers, while on the contrary, the nitrate and cellulose content were decreased, and the N1 treatment showed the best effect. Moreover, the yield had a significant positive correlation with Bacillus. Overall, nitrogen reduction with bio-organic fertilizers, especially full-effective “No. 1” enriched with Bacillus, could alter the soil microbial community structure and effectively improve soil fertility, which in turn enhanced the yield and quality of radish. An application of Bacillus bio-organic fertilizer was an effective strategy to improve soil quality and vegetable safety.